2019
DOI: 10.14334/jitv.v24i1.1923
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of pod colour with the quality of Indigofera zollingeriana

Abstract: <em>Indigofera zollingeriana</em> (Indigofera) plant is potential feed ingredients. The propagation of this plant is through seed. The low quality of seed is a problem in its development. This study was aimed to evaluate the relationship of pod colour with quality of Indigofera seeds. The study was designed in a complete randomized design consisting of four pod colours and four replications, namely: P<sub>1</sub>= green, P<sub>2</sub>= brownish green, P<sub>3</sub&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
(7 reference statements)
1
3
1
Order By: Relevance
“…The highest seed germination of Indigofera plants that grew due to irradiation treatment in this study was obtained at a dose of 400 Gy (60%). The results obtained are almost comparable to those reported by Hutasoit [18] of 62% in the study of Indigofera seed selection based on pod color. The results obtained from the growth of this plant are still below the SNI standard, a minimum of 75% (Directorate General of Food Crops 1991).…”
Section: Seed Germinationsupporting
confidence: 88%
“…The highest seed germination of Indigofera plants that grew due to irradiation treatment in this study was obtained at a dose of 400 Gy (60%). The results obtained are almost comparable to those reported by Hutasoit [18] of 62% in the study of Indigofera seed selection based on pod color. The results obtained from the growth of this plant are still below the SNI standard, a minimum of 75% (Directorate General of Food Crops 1991).…”
Section: Seed Germinationsupporting
confidence: 88%
“…Likewise for the number seed/pods, the average number owned is five seeds/pod, mostly in the P 3 (5.35). This result is higher than that reported by Hutasoit [7] with the report by Logo [9], that pod size affects to the characteristics of the seeds in soybean plants.…”
Section: Morphological Characteristics Of Indigofera Pods and Seedscontrasting
confidence: 73%
“…Following up on previous research [7] who tested different pod colors on Indigofera seeds showed that the color of brownish green pods had higher sprouts (62%). Apart from different pod colors according to our observations at harvest time, there are also differences in the size of Indigofera pods, including: 3.5 cm, 4 cm, 4.5 cm, and 5.5 cm.…”
Section: Icasimentioning
confidence: 87%
See 1 more Smart Citation
“…Indigofera zollingeriana has been commonly used as a feed supplement or as a sole forage to produce a good growth rate of goats [4] and improve milk production and efficiency of feed and nutrient utilization [5]. The use of Indigofera sp in a forage-based ration can increase feed intake, digestibility, IOP Publishing doi:10.1088/1755-1315/1341/1/012045 2 ration efficiency, and daily body weight gain in goats [6].…”
Section: Introductionmentioning
confidence: 99%